Otorhinolaryngology Out-Patient Practice in the “Post”-COVID-19 Era: Ensuring a Balance Between Service and Safety - Jose Florencio Lapeña; Franco Louie Abes; Mark Anthony Gomez; Cesar Vincent Villafuerte; Rodante Roldan; Philip Fullante; Ryner Jose Carrillo; Justin Elfred Lan Paber; Armando Isla; Rose Alcances-Inocencio; Jose Benedicto Cabazor; Ruzanne Caro; et al. (Philippine Journal of Otolaryngology Head and Neck Surgery, 2020)
Objective: To review available resources and provide evidence-based recommendations that may optimize otorhinolaryngologic out-patient health care delivery in the “post”-COVID-19 era while ensuring the safety of our patients, healthcare workers and staff.